Heterogeneous electrode processes and localized corrosion - Tan, Yongjun, 1963- (Wiley series in corrosion, 2013)
"This book covers the areas of electrochemical heterogeneity and electrode inhomogeneity and their effects on nonuniform electrode processes, in particular, localized corrosion. It covers the fundamentals, experimental methods, and engineering aspects of electrochemical heterogeneity"--